1993
DOI: 10.1111/j.1365-4362.1993.tb02812.x
|View full text |Cite
|
Sign up to set email alerts
|

Friction Amyloidosis: A Variant or an Etiologic Factor in Amyloidosis Cutis?

Abstract: The role of friction in the causation of lesions that resemble amyloidosis cutis morphologically is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…It seems likely that the mechanism of pigmentation is a response to repeated damage of the basal layer of the epidermis as a result of squeezing the epidermis between the washing brush above and the bone below. Similar pigmentation has been described following chronic rubbing with nylon washing brushes in Japan (2–6), Mexico (7), India (8), and China (9).…”
Section: Discussionsupporting
confidence: 67%
“…It seems likely that the mechanism of pigmentation is a response to repeated damage of the basal layer of the epidermis as a result of squeezing the epidermis between the washing brush above and the bone below. Similar pigmentation has been described following chronic rubbing with nylon washing brushes in Japan (2–6), Mexico (7), India (8), and China (9).…”
Section: Discussionsupporting
confidence: 67%
“…The objects causing the friction included sponges used during bathing, nylon brushes, plant sticks and leaves, and towels. The possible role of friction in the causation of cutaneous amyloidosis has been reported in several previous reports 1–5,9 . One study of three patients 1 found nylon brushes, plastic objects, towels and fingernails to be the most common objects causing friction.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, the limitations of histochemical stains in the detection of amyloid and the usefulness of electron microscopy in the diagnosis of the condition have been recognized 1 . The role of scratching and friction in the causation of this condition has been reported in other studies 3–5 …”
Section: Introductionmentioning
confidence: 95%
“…Our patient’s occupation involved bending wires with her thumb, index and middle fingers, which led us to postulate a role for chronic friction or pressure in the localization of her lesions. The role of friction in amyloidosis has previously been explored in lichen amyloidosis, 8–10 suggesting that in at least one third of cases, local friction correlated with the site of amyloid deposits. The occupations or hobbies of the previous two cases of localized acquired cutis laxa were not reported.…”
Section: Discussionmentioning
confidence: 99%